2017
DOI: 10.1177/1932296817693253
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Glucose Monitoring Use in Type 1 Diabetes: Longitudinal Analysis Demonstrates Meaningful Improvements in HbA1c and Reductions in Health Care Utilization

Abstract: Background: Real-time continuous glucose monitoring (rtCGM) improves glycemic control in type 1 diabetes (T1D) patients treated with continuous subcutaneous insulin infusion (CSII). However, the benefits of rtCGM in T1D patients treated with multiple daily insulin injection (MDI) therapy has not been well studied. We explored the effects of rtCGM versus self-monitoring of blood glucose (SMBG) on clinical outcomes within a large T1D population treated with either CSII or MDI therapy. Methods: This retrospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 33 publications
3
54
2
2
Order By: Relevance
“…In contrast to the documented benefits of CGM use in adult patients with diabetes, studies specifically involving paediatric patients have shown more inconsistent findings . This disparity in benefits may be partly as a result of even more inconsistent use than that observed in adults.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…In contrast to the documented benefits of CGM use in adult patients with diabetes, studies specifically involving paediatric patients have shown more inconsistent findings . This disparity in benefits may be partly as a result of even more inconsistent use than that observed in adults.…”
Section: Introductionmentioning
confidence: 89%
“…One of the key barriers to long-term adoption of CGM technology has been tiredness of use, with patients reporting discontinuation in the first year because of many reasons including perceived inaccuracy (53%), wear discomfort (47%), insertion pain (31%) and skin irritation (41%). 2 In contrast to the documented benefits of CGM use in adult patients with diabetes, 3,4 studies specifically involving paediatric patients have shown more inconsistent findings. 5 This disparity in benefits may be partly as a result of even more inconsistent use than that observed in adults.…”
mentioning
confidence: 99%
“…The cost-effectiveness of CGM and closed-loop systems is considered in more detail elsewhere. [133][134][135] CGM also serves as a tool that can assist evaluation of new and improved methods for medical therapy of diabetes, for earlier detection of prediabetes, and earlier diagnosis of diabetes.…”
Section: Hypoglycemiamentioning
confidence: 99%
“…From a clinical point of view, the use of real-time CGM showed meaningful improvements in glycated hemoglobin (HbA1c) [45] and a reduction of hypoglycemic events [46]. Moreover, the use of CGM sensors was demonstrated to improve quality of life [47], e.g., by reducing fear of hypoglycemia [48], and resulted in being cost-effective in long-term projections [45].…”
Section: Clinical Impact Of Cgm Sensorsmentioning
confidence: 99%
“…From a clinical point of view, the use of real-time CGM showed meaningful improvements in glycated hemoglobin (HbA1c) [45] and a reduction of hypoglycemic events [46]. Moreover, the use of CGM sensors was demonstrated to improve quality of life [47], e.g., by reducing fear of hypoglycemia [48], and resulted in being cost-effective in long-term projections [45]. Although all these benefits have been extensively proven, there are still many other factors that influence patient and clinician confidence in the use of CGM, such as accuracy, reliability, usability, duration of sensor life, and calibration requirements [49].…”
Section: Clinical Impact Of Cgm Sensorsmentioning
confidence: 99%